2012
DOI: 10.1371/journal.pone.0051075
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Indicator of Agricultural Management for Soil under No-Till Crop Production

Abstract: The rise in the world demand for food poses a challenge to our ability to sustain soil fertility and sustainability. The increasing use of no-till agriculture, adopted in many areas of the world as an alternative to conventional farming, may contribute to reduce the erosion of soils and the increase in the soil carbon pool. However, the advantages of no-till agriculture are jeopardized when its use is linked to the expansion of crop monoculture. The aim of this study was to survey bacterial communities to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 59 publications
7
63
0
3
Order By: Relevance
“…This soil, under good agricultural practices, contains diverse indigenous microorganisms (Figuerola et al, 2012). The soil was collected from the Pampean Region, Buenos Aires, Argentina.…”
Section: Plant Productivity and Nitrogen Determinationsmentioning
confidence: 99%
“…This soil, under good agricultural practices, contains diverse indigenous microorganisms (Figuerola et al, 2012). The soil was collected from the Pampean Region, Buenos Aires, Argentina.…”
Section: Plant Productivity and Nitrogen Determinationsmentioning
confidence: 99%
“…However, after several successive years of these reduced tillage (i.e., only tilling to a depth less than 20 cm) or no-tillage systems, subsoil compaction at 15-30 cm depths appears to be increasing due to the increase of bulk density resulted by water infiltration and sowing and harvesting machineries (Kong et al, 2010;. Furthermore, although adopting some form of conservation tillage is generally beneficial for increasing SOC levels and sequestering C in the topsoil (Ussiri and Lal, 2009;Martinez et al, 2013), the reduced incorporation of crop residues has been reported to increase subsoil bulk density and reduce crop root proliferation (Figuerola et al, 2012), thereby limiting water and nutrient availability (He et al, 2009) and resulting in reduced crop yields (Bhatia et al, 2010;Arvidsson et al, 2014). For example, many studies have demonstrated that decreases in crop yield in response to long-term NT adoption may be caused by reduced seed germination and emergence, lower early season soil temperatures, below-optimal plant populations, poorer weed control, delayed plant development and maturity, increased grain moisture content, and lower grain yield potential following adoption of NT (Toliver et al, 2012;Kovar et al, 1992;Fortin, 1993;Swan et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The Indicator Value method has been successfully applied to test for indicator species using metagenomic data [30] of tilled vs. non-tilled crop production. Its application to our datasets is questionable as the classification of pesticide impact is normally based, among other parameters, on the effect on taxonomic diversity at higher (usually class or phylum) levels.…”
Section: Discussionmentioning
confidence: 99%